The relationship between capital structure and financial performance: evidences from consumer product industry in Malaysia / Masezahati Rudin - Rudin, Masezahati (2017)
Capital structure in the company is very important as it shows the investors on the types of financing are the company use and prior research found that there are positive and negative impact on company financial performance. Therefore, the objectives of this paper is to determine the capital structure effect towards financial performance of the company under consumer product sector that listed in Bursa Malaysia. Data were collected from the company annual report covering the period of 2010 - 2014. Variables use to measure the financial performance of companies are return on asset ratio (ROA) and return on equity ratio (ROE). While variable use to measure the capital structure are long term debt to total asset, short term debt to total asset debt to equity ratio.